Controlled lateral buckling of subsea pipelines triggered by imposed residual initial imperfections. (1st August 2021) - Wang, Zhenkui; Duan, Nuo; Soares, C. Guedes
Abstract: The phenomenon of lateral buckling for subsea pipelines may result from the build-up of axial force along the pipeline induced by high temperature difference. The excessive lateral deflection resulting from lateral buckling may lead to fracture failure of welds or collapse of the pipeline. In this study, controlled lateral buckling triggered by imposed residual initial imperfections along the pipeline at designed locations is investigated. Mathematical models are proposed and analytical solutions are derived for subsea pipelines with the imposed residual initial imperfections, which are validated by comparing with FEA results. The typical behaviour of lateral buckling triggered by unstressed or stressed initial imperfection is compared. The effect of the amplitude and wavelength of the initial imperfection and the distance between adjacent initial imperfections on lateral buckling behaviour is discussed. The results show that an appropriate wavelength of initial imperfection should be selected to mitigate the maximum stress in the post-buckling state and to avoid snap-through buckling phenomenon. Another efficient way to reduce the displacement amplitude and maximum stress is to reduce the distance between adjacent initial imperfections, i.e. more buckles be triggered. Highlights: A mathematical model is proposed for lateral buckling triggered by the imposed residual initial imperfection. The typical behaviour of lateral buckling triggered by unstressed or stressed initial imperfection is compared. Snap-through phenomenon between pre-buckling and post-buckling is analysed. The effect of the imperfection and the distance between adjacent imperfections on lateral buckling behaviour is discussed.